Tenth Five Year Plan 2002-2007 and Annual Plan 2002-2003 [Volume-I] National Capital Territory of Delhi - Planning Commission (Planning Commission, 2002)
Geographically, Delhi is located in the heart of northern India, surrounded by the States of Haryana and Uttar Pradesh. It covers area of 1483 sq. kms. of which 591.91 sq. kms. is rural and 891.09 sq. kms. is urban. Due to rapid urbanisation, the rural area is diminishing gradually in Delhi as is evident from the following table.
Planning Department, Govt. of NCT of Delhi